Racial Differences in Ischemic and Hemorrhagic Stroke: An Ecological Epidemiological Study - Kang, Dong-Seon; Yang, Pil-Sung; Kim, Daehoon; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Sung, Jung-Hoon; Pak, Hui-Nam; Lee, Moon-Hyoung; Lip, Gregory Y H; Joung, Boyoung (Thrombosis and haemostasis, 2024)
This study aimed to evaluate racial differences in the incidence of stroke by conducting an ecological epidemiological study using UK Biobank and Korean nationwide data. This study used individual data from the Korean National Health Insurance Service-Health Screening and UK Biobank, which included participants who underwent health examinations between 2006 and 2010. We included 112,750 East Asians (50.7% men, mean age: 52.6 years) and 210,995 Caucasians (44.7% men, mean age: 55.0 years) who were not diagnosed with atrial fibrillation, cardiovascular diseases, chronic kidney disease, chronic obstructive pulmonary disease, or cancer. The primary outcome was defined as a composite of ischemic and hemorrhagic stroke. East Asians tended to have a lower body mass index (23.7 vs. 26.4 kg/m , < 0.001) and a higher proportion of participants who did not engage in moderate-to-vigorous physical activity (49.6% vs. 10.7%, < 0.001) than Caucasians. During the follow-up, East Asians had higher 5-year incidence rates (presented as per 1,000 person-years) for primary outcome (1.73 vs. 0.50; IR ratio [IRR]: 3.48, 95% confidence interval [CI]: 3.13-3.88), ischemic stroke (1.23 vs. 0.33; IRR: 3.70, 95% CI: 3.25-4.21), hemorrhagic stroke (0.56 vs. 0.18; IRR: 3.20, 95% CI: 2.67-3.84), and atrial fibrillation-related stroke (0.19 vs. 0.09; IRR: 2.04, 95% CI: 1.55-2.68). Based on this ecological epidemiological study, racial differences in stroke incidence were robust to a variety of statistical analyses, regardless of the subtype. This suggests the need for region-specific approaches to stroke prevention.